Alterações morfofuncionais e metabólicas no teleósteo de água doce matrinxã, Brycon cephalus (Günther, 1869) exposto ao organofosforado metil paration (Folisuper 600BR®) - Barreto, Tiago de Rezende (2006)
The xenobiotics influxes into the aquatic systems are continuous increasing in Brazil due to their use in the agriculture and to control insects in aquaculture. In the present study was evaluated if the exposure of the freshwater teleost fish matrinxã (Brycon cephalus) to sublethal concentration of the organophosphorus pesticides methylparathion (MP) induce morphofunctional changes in the interrenal cells and in the gills as well as metabolic changes in this species. Specimens of matrinxã were divided in two groups with 7 animals in each one and kept in aquarium with 200L. One of them was the control group and was kept in water without the presence of MP and the other was the MP group and was exposed to 2 ppm of methyl parathion during 96 hours. Food was suspended for both groups 24 hours before the transference of fish to their respective aquarium and fish were maintained 12 hours in the aquarium for acclimatizing before experiments. Fish exposed to MP reduced the swimming activity and histological changes were observed in the interrenal cells as increasing of cell and nucleus areas and also the ration nucleus area/cellular area indicating an increase of cell activity, which cortisol is the major corticoid produced by these cells. Plasma cortisol also increased in fish exposed to MP. The histological changes in the gills were classified as slight to moderate. The hematological analysis support it hypothesis as no change was found in the blood hematology and in their indexes. Glucose concentration in plasma increased in fish exposed to MP while it decreased in the liver. Lactate concentration decreased in plasma and liver of animals exposed to MP suggesting an absence of internal hypoxia and supports the indication that the gill function was partially maintained. Piruvate concentration did not change, but the ammonia levels increased in plasma and liver in fish exposed to 96h to MP. These results suggest that gluconeogenesis occurred and the high level of glucose was kept high to maintain the energy supply to tissues. In conclusion, the results evidenced that the exposure to 2 ppm of methyl parathion caused an increase of area of interrenal cells suggesting the activation of Hypothalamic-Pituitary-Interrenal axis e slight to moderate changes in the gill tissues although they partially kept their function. The changes in liver metabolism are probably related to the increase of energy demand of fish.